المؤتمر الأفخارستي الدولي الثلاثون بقرطاج (7-11 ماي 1930) - عمان, سعيدة (جامعة الوادي - University of Eloued, 2022)
نظمت فرنسا بالاتفاق مع الكنيسة مؤتمرا افخارستيا بقرطاج في الفترة 7-11 ماي 1930، ونظرا لما يمثله الحدث من أهمية لدى المسيحيين الكاثوليك، فإن التظاهرة شهدت اهتماما كبيرا من الفرنسيين، المنقسمين بين مؤيد ومعارض، فأيدته الصحف الاستعمارية ذات النزعة الدينية الكاثوليكية، وأعدته حملة صليبية على تونس، ومناسبة لإحياء المسيحية واستئناف فرنسا للرسالة الحضارية الرومانية في إفريقيا، وعارضته الصحف الاشتراكية واعتبرته خروج فرنسا عن مبادئها العلمانية؛ وذلك لعدم احترامها لحقوق الانسان وحرية الأديان. أما الصحافة التونسية فقد نددت بالمؤتمر ومنظميه ، وكذلك بالنفقات الباهظة التي أخذت من أموال الخزينة التونسية لتمويل تظاهرة مسيحية ليس لها أيّ فائدة للشعب التونسي، كما اعتبرته استمرارا لسياسة فرنسا الإدماجية، لذا عملت على كشف مراميه السياسية وأبعاده الدينية، ودعت الى ضرورة مجابهته. France, in agreement with the Church, organized an Eucharist conference in Carthage from 7-11 May 1930, and given the importance the event represented to Catholic Christians, the demonstration witnessed great interest from the French, divided between supporters and opponents, and colonial newspapers with a Catholic religious tendency supported it, and considered it a crusade. Against Tunisia, an occasion to revive Christianity and France's resumption of the Romanian civilization message in Africa. Socialist newspapers opposed it and considered it a departure for France from its secular principles, due to its lack of respect for human rights and freedom of religion. As for the Tunisian press, it denounced the conference and its organizers, , as well as the exorbitant expenditures taken from Tunisian treasury funds to finance a Christian demonstration that has no benefit to the Tunisian people, as it considered it a continuation of France's integration policy, so it worked to reveal its political goals and religious dimensions, and called for the need to confront it.
مقال
Keywords: المؤتمر الافخارستي ; قرطاج ; الصحف الاستعمارية ; الصحافة التونسية ; العلمانية; Eucharist Congress; Carthage; colonial newspapers; Tunisian press; secularism